Acid and Enzymatic Hydrolyses of Rice Bran for Bioethanol Production - Dewi Yuliani; Khoirul Achmad Julianto; Akyunul Jannah (ALCHEMY:Journal of Chemistry, 2018)
Rice bran is one among many agricultural by-products containing ~50-60 wt.% of carbohydrate. The carbohydrate is a prominent sugar source for bioethanol production. The objective of this research was to study bioethanol production from rice bran by acid and enzymatic treatment. The variations of acid used were dilute hydrochloric acid and sulphuric acid, while variations of enzyme used were amylolytic and cellulolytic enzyme. Ethanol production of acid-hydrolyzed rice bran was 24.95±1.61% (v/v) by hydrochloric acid and 29.57±2.04% (v/v) by sulphuric acid. Ethanol produced by enzymatic hydrolysis was quite low i.e. 6.7±0.04%, and 8.86±0.29% (v/v) for amylolytic and cellulolytic hydrolysate, respectively. Keywords: Bioethanol, rice bran, acid hydrolysis, enzymatic hydrolysis